Challenges of Veiled Woman in Society - Sabrina, Rifdah; Najmah, Lailan; Afrina, Meti (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2020)
This research aims to analyze the challenges faced by women who wear the veil in society. This research uses a qualitative method with a phenomenological approach, research data was taken through direct interviews with ten informants. All interview data was then analyzed thematically using Miles and Huberman qualitative data analysis. Research findings show that there are four challenging factors faced by women who wear the niqab, namely i) maintaining consistency in wearing the niqab, ii) difficulty in carrying out activities, iii) not getting permission from parents, iv) getting ridiculed by society. The results of this research can be used as initial data for subsequent researchers in studying different issues related to this problem as well as various other issues that are relevant to this context.